Digital divides and children in Europe - Panayiota Tsatsou (Kids Online, 2009)
This article uses the EU Kids Online data collection and Eurobarometer 2008 to examine the extent and nature of digital divides among children in Europe today. It finds that, although gaps in internet access and use have decreased in Europe, they still exist. Differences are significant between countries as well as within countries in Europe, with Southern Europe in particular lagging behind. Socioeconomic factors still influence the degree of internet access for children and young people in Europe. Although this influence starts to fade as we move the focus towards specific aspects of internet usage, such as frequency and amount of use, evidence in some countries supports a correlation between socioeconomic indicators and the online opportunities taken up by children. Finally, as regards ‘digital generation’ and ‘generational gaps’, empirical research in Europe has shown that although a lack of parental internet experience may inhibit children from using internet technologies, additional socialising factors such as schools, peer groups and public opinion can be enough to enable a child to take up internet use.